High intracellular Zn(2+) ions modulate the VHR, ZAP-70 and ERK activities of LNCaP prostate cancer cells - Wong, P.F.; AbuBakar, Sazaly (2008)
Malignant prostate tissues have markedly reduced zinc (Zn(2+)) contents in comparison to non-malignant tissues. In this study, we restored a high intracellular Zn(2+) level to LNCaP prostate cancer cells by culturing the cells in a growth medium supplemented with a supraphysiological concentration of Zn(2+) (10 mu g/ml) over 5 weeks. The intracellular Zn(2+) level increased in the Zn(2+)-treated cells, and there was a marked increase in the presence of zincosomes, a Zn(2+)-specific intracellular organelle. The proliferation rate of the Zn(2+)-treated cells was markedly reduced. There was also a significant increase (36.6 +/- 6.4) in the total tyrosine phosphorylated proteins. Vaccinia H1-related (VHR) phosphatase, zeta chain-associated protein-70 (ZAP-70) kinase and phosphorylated extracellular signal-regulated protein kinase 1 and 2 (p-ERK 1 and 2) were also present in higher abundance. Treatment with TPEN, which chelates Zn(2+), reduced the abundance of VHR phosphatase and ZAP-70 kinase, but increased the abundance of p-ERK 1. However, the TPEN treatment restored the Zn(2+)-treated LNCaP cell proliferation to a rate comparable to that of the non Zn(2+)-treated cells. These results highlight the importance of a high intracellular Zn(2+) content and the VHR/ZAP-70-associated pathways in the modulation of LNCaP prostate cancer cell growth.